Effects of a lighter, smaller football on acute match injuries in adolescent female football: a pilot cluster-randomized controlled trial - Zebis, M. K.; Thorborg, K.; Andersen, L. L.; Moller, M.; Christensen, K. B.; Clausen, M. B.; Hölmich, P.; Wedderkopp, N.; Andersen, T. B.; Krustrup, P. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The high injury incidence during match-play in female adolescent football is a major concern. In football, males and females play matches with the same football size. No studies have investigated the effect of football size on injury incidence in female adolescent football. Thus, the aim of the present study was to investigate the effects of introducing a lighter, smaller football on the injury pattern in female adolescent football. METHODS: We conducted a pilot cluster randomized controlled trial including 26 football teams representing 346 adolescent female football players (age 15-18 years). The teams were randomized to a new lighter, smaller football (INT, N.=12 teams) or a traditional FIFA size 5 football (CON, N.=14 teams) during a full match-season. Acute time-loss injuries and football-exposure during match-play were reported weekly by text-message questions and verified subsequently by telephone interview. RESULTS: In total, 46 acute time-loss injuries were registered (5 severe injuries), yielding an incidence rate of 15.2 injuries per 1000 hours of match-play (95% CI: 8.5-27.2) in INT and 18.6 injuries per 1000 hours of match-play (95% CI: 14.0-24.8) in CON. The estimated 22% greater injury incidence rate risk (IRR: 1.22 [95% CI: 0.64-2.35]) in the CON group was not significant. With an IRR of 1.22, a future RCT main study would need to observe 793 acute time-loss injuries during match-play, in order to have a power of 80%. CONCLUSIONS: A large-scaled RCT is required to definitively test for beneficial or harmful effects of a lighter, smaller football in adolescent female football.